PERSPEKTIF HADIS TENTANG AKTIVITAS MEMANCING: LARANGAN PERJUDIAN DAN KELALAIAN TERHADAP KEWAJIBAN - Hoirul Anam (JUTEQ: JURNAL TEOLOGI & TAFSIR, 2025)
Fishing is a popular recreational activity among many people. From an Islamic perspective, recreation is permitted as long as it does not violate Sharia law and does not interfere with religious obligations. This study aims to examine fishing from the perspective of hadith, particularly in relation to the prohibition of gambling (maisir) and the dangers of neglecting religious obligations. The research method used is a thematic study (maudhu‘i) by compiling relevant hadiths from major books, then analysing them normatively and contextually. The results of the study show that fishing as a recreational activity is permissible (mubah) if done with good intentions, such as seeking livelihood or healthy entertainment. However, this activity becomes haram if it is used as a form of gambling, as stated in QS. Al-Maidah verse 90 and the hadith narrated by Muslim about the prohibition of games involving betting. In addition, fishing should not neglect religious obligations, especially prayer, which is the pillar of religion as stated in the hadith narrated by Baihaqi. The hadith also emphasises the principles of Islamic recreational ethics, namely maintaining a balanced life, environmental cleanliness, and using recreation as a means of character education. Thus, recreational activities such as fishing can be positive and even part of worship if done in accordance with Islamic manners. Conversely, if it contains elements of gambling or neglects obligations, then such activities are contrary to the principles of Sharia.